Variables affecting the emergence of untaught equivalence relations in children with and without autism. (3rd March 2016) - McLay, Laurie; Church, John; Sutherland, Dean
Abstract: Objective : This study examined the formation of equivalence classes among children with ASD and typically developing children. Design : A single-subject AB and BA design was used. Methods : Two of the six equivalence relations were taught. Participants were then tested to determine whether the remaining four equivalence relations were acquired without teaching. Half of the children were taught naming responses first, then selecting responses. Half were taught in the reverse order. Results : Five out of 10 participants with ASD demonstrated the emergence of all four untaught relations. The remaining five participants showed variability. Nine of the 10 typically developing children demonstrated emergence of all untaught relations. Variation in teaching conditions had no significant effect on outcomes. Conclusions : Many children with ASD are capable of generalising to untaught equivalence relations. The results fail to support the claim that acquisition of naming responses is a pre-requisite for the emergence of untaught equivalence relations.